2004
DOI: 10.1590/s0102-695x2004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Atividades antinociceptiva e antiinflamatória do óleo essencial de cascas de Duguetia lanceolata St. Hil., Annonaceae

Abstract: ResumoO presente trabalho avaliou as atividades antinociceptiva e antiinflamatória do óleo essencial de cascas de Duguetia lanceolata. Para isto, foram realizados os testes de contorções abdominais induzidas por ácido acético; tempo da lambida da pata induzida por formalina; e edema de pata induzido por carragenina. O número de contorções abdominais (DE 50 No presente trabalho, os métodos de contorções abdominais, tempo de lambida da pata e edema de pata foram utilizados para avaliar as atividades antinocic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 2 publications
(2 reference statements)
3
15
0
2
Order By: Relevance
“…Natural compounds have potential therapeutic effects such as antimicrobial Oliveira et al, 2006) antinociceptive, and antiinflammatory activities (Sousa et al, 2004). These effects are probably due to great structural diversity of the essential oils constituents in plants (Calixto, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds have potential therapeutic effects such as antimicrobial Oliveira et al, 2006) antinociceptive, and antiinflammatory activities (Sousa et al, 2004). These effects are probably due to great structural diversity of the essential oils constituents in plants (Calixto, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This species is native in this country and found in the Cerrado and Atlantic Forest, especially in Minas Gerais, Mato Grosso and São Paulo States. In folk medicine, this plant has been used as an anti-inflammatory, cicatrizing and antimicrobial agent [9]. Pharmacological studies have demonstrated that D. lanceolata presented antinociceptive, anti-inflammatory and antiplasmodial activities [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…can be inhaled to combat influenza [1]. Many essential oils of Annonaceae have antiprotozoal [2,3], antimicrobial [3], anti-inflammatory, cytotoxic [4] and antinociceptive [5] effects. These considerations confirm the importance of chemical and biological investigations of essential oils of species this family as a source of bioactive compounds.…”
mentioning
confidence: 99%